Local Stiffness Effect on Ferromagnetic Response of Nanostructure Arrays in Stretchable Systems. Issue 2 (2nd November 2018) - Challab, Nabil; Zighem, Fatih; Faurie, Damien; Haboussi, Mohamed; Belmeguenai, Mohamed; Lupo, Pierpaolo; Adeyeye, Adekunle O.
Abstract : The control of magnetoelastic effects in magnetic media, their improvement or even their minimization according to the intended applications is a current problem. In this work, the effect of the elastic strain on the magnetic properties of Ni60 Fe40 continuous films and nanowires deposited on Kapton® substrates has been investigated. For this purpose, piezoactuation mechanical tests are performed in situ with ferromagnetic resonance measurements. It has been observed that the continuous thin film and the array of nanowires exhibit distinct behaviors in the presence of an elastic strain field. Precisely, the induced magnetoelastic anisotropy is much less pronounced in the case of nanowires. This difference in behavior has been explained/investigated based on finite element simulations. These latter revealed that the average strain transmitted from flexible substrate to magnetic medium is less important in the case of nanowires compared to continuous film. This lack of strain transfer/transmission is related to the relative amount of free surface of the nanostructures combined with a strong mechanical contrast between Ni60 Fe40 and Kapton (viz., a deposit relatively much more stiffer than the substrate). This important effect can be exploited in the future by controlling and optimizing geometries of nanostructures. Abstract : Performed ferromagnetic resonance measurements on continuous films and nanowires deposited on piezoactuated Kapton substrates show different magnetic properties. This difference has been explained by the transmitted strain, computed by finite element, which is less important in the case of nanowires because of the relative amount of free surface.